The Crisis in Urban Documentation: "The Shame of the Cities" Revisited - Baskerville, Peter; Gaffield, Chad (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1984)
Despite the importance of local public records as a resource for the research interests of many different disciplines, general literature suggests that there is currently little effort being made to ensure the preservation of these documents for both current and future use. Unless this gap is bridged in the near future, locally generated records will be a lost resource. Traditional reliance on archivists for the care and preservation of these materials is misplaced, given the problems which currently beset the archival profession. An interdisciplinary initiative is required if the crisis in local government records is to be met. In the hope of encouraging others, this paper reports on one such initiative. The Vancouver Island Project is a systematic inventory of surveying all local public records on Vancouver Island. When completed, the Project will provide a machine-readable, updateable, descriptive/evaluative list of this material. In the process it will attempt to encourage the development of better maintenance of these documents by their local custodians. The Project will provide a structure from which classification and retention programs can emerge.